FEATURES OF PREIMPLANTATION GENETIC DIAGNOSIS OF EMBRYOS OBTAINED FROM MEN WITH SEVERE SPERMATOGENESIS FAILURES - Feskov O. O. (Вісник проблем біології і медицини, 2019)
Recently high attention in the reproductive medicine is paid to the paternal genome failures. Assisted reproductive techniques, and especially intracytoplasmic sperm injection, allow couples whose sperm characteristics are impaired to obtain a pregnancy, whereas a few years ago, these couples would have had to use sperm donation in order to obtain their child. The effect of spermatogenesis failures on the process of the blastocysts formation and embryos euploidy in IVF practice was studied in present work. Preimplantation genetic diagnostics was carried out for 229 blastocysts obtained from 67 men with low reproductive function by the methods of assisted reproductive techniques. It was showed the relationship between the failures in male reproductive function and the quality of embryos in IVF cycles. The effect of the concentration of spermatozoa in the ejaculate on the euploidy of blastocysts in ART is proved (rs = 0.151). A strong positive correlation between the blastocyst morphology and such sperm parameters as motility and the morphology of spermatozoa in the ejaculate is demonstrated (rs = 0.184 and rs = 0.170, respectively). Poor blastocyst morphology is positively correlated with the presence of aneuploidy in the embryo (rs = 0.183). The observed data indicate that the detection of significant deviations of the microscopic sperm parameters is an indication for a preimplantation genetic diagnosis (preimplantation genetic testing for aneuploidies) of embryos in IFV cycles. This conclusion is of great practical significance, as the results of the most published studies demonstrated no association between the embryos euploidy and sperm quality. The obtained results regarding the correlation of the blastocysts morphology with the presence of aneuploidy can be significant in practice as the high quality of the embryos morphology does not always correlate with the high frequency of implantation.